Neratinib after trastuzumab-based adjuvant therapy in patients with HER2-positive breast cancer (ExteNET): a multicentre, randomised, double-blind, placebo-controlled, phase 3 trial. Issue 3 (March 2016) - Chan, Arlene; Delaloge, Suzette; Holmes, Frankie A; Moy, Beverly; Iwata, Hiroji; Harvey, Vernon J; Robert, Nicholas J; Silovski, Tajana; Gokmen, Erhan; von Minckwitz, Gunter; Ejlertsen, Bent; Chia, Stephen K L; et al.
Summary: Background: Neratinib, an irreversible tyrosine-kinase inhibitor of HER1, HER2, and HER4, has clinical activity in patients with HER2-positive metastatic breast cancer. We aimed to investigate the efficacy and safety of 12 months of neratinib after trastuzumab-based adjuvant therapy in patients with early-stage HER2-positive breast cancer. Methods: We did this multicentre, randomised, double-blind, placebo-controlled, phase 3 trial at 495 centres in Europe, Asia, Australia, New Zealand, and North and South America. Eligible women (aged ≥18 years, or ≥20 years in Japan) had stage 1–3 HER2-positive breast cancer and had completed neoadjuvant and adjuvant trastuzumab therapy up to 2 years before randomisation. Inclusion criteria were amended on Feb 25, 2010, to include patients with stage 2–3 HER2-positive breast cancer who had completed trastuzumab therapy up to 1 year previously. Patients were randomly assigned (1:1) to receive oral neratinib 240 mg per day or matching placebo. The randomisation sequence was generated with permuted blocks stratified by hormone receptor status (hormone receptor-positive [oestrogen or progesterone receptor-positive or both] vs hormone receptor-negative [oestrogen and progesterone receptor-negative]), nodal status (0, 1–3, or ≥4), and trastuzumab adjuvant regimen (sequentially vs concurrently with chemotherapy), then implemented centrally via an interactive voice and web-response system. Patients, investigators, and trial sponsors were masked to treatment allocation. The primary outcome was invasive disease-free survival, as defined in the original protocol, at 2 years after randomisation. Analysis was by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT00878709 . Findings: Between July 9, 2009, and Oct 24, 2011, we randomly assigned 2840 women to receive neratinib (n=1420) or placebo (n=1420). Median follow-up time was 24 months (IQR 20–25) in the neratinib group and 24 months (22–25) in the placebo group. At 2 year follow-up, 70 invasive disease-free survival events had occurred in patients in the neratinib group versus 109 events in those in the placebo group (stratified hazard ratio 0·67, 95% CI 0·50–0·91; p=0·0091). The 2-year invasive disease-free survival rate was 93·9% (95% CI 92·4–95·2) in the neratinib group and 91·6% (90·0–93·0) in the placebo group. The most common grade 3–4 adverse events in patients in the neratinib group were diarrhoea (grade 3, n=561 [40%] and grade 4, n=1 [<1%] vs grade 3, n=23 [2%] in the placebo group), vomiting (grade 3, n=47 [3%] vs n=5 [<1%]), and nausea (grade 3, n=26 [2%] vs n=2 [<1%]). QT prolongation occurred in 49 (3%) patients given neratinib and 93 (7%) patients given placebo, and decreases in left ventricular ejection fraction (≥grade 2) in 19 (1%) and 15 (1%) patients, respectively. We recorded serious adverse events in 103 (7%) patients in the neratinib group and 85 (6%) patients in the placebo group. Seven (<1%) deaths (four patients in the neratinib group and three patients in the placebo group) unrelated to disease progression occurred after study drug discontinuation. The causes of death in the neratinib group were unknown (n=2), a second primary brain tumour (n=1), and acute myeloid leukaemia (n=1), and in the placebo group were a brain haemorrhage (n=1), myocardial infarction (n=1), and gastric cancer (n=1). None of the deaths were attributed to study treatment in either group. Interpretation: Neratinib for 12 months significantly improved 2-year invasive disease-free survival when given after chemotherapy and trastuzumab-based adjuvant therapy to women with HER2-positive breast cancer. Longer follow-up is needed to ensure that the improvement in breast cancer outcome is maintained. Funding: Wyeth, Pfizer, Puma Biotechnology.